TINGKAT KEPUASAN PETANI TERHADAP KINERJA PENYULUH DI DESA PURWOSARI KECAMATAN MIJEN KOTA SEMARANG - Akhmad Aqil Mushoddaq; Sumekar, Wulan; Nurfadillah, Suryani (JURNAL LITBANG PROVINSI JAWA TENGAH, 2022)
The Agricultural extension activities provides some agricultural extension services to farmers. The poor performance of the agricultural extension than the farmer’s expectations has an impact on the level of farmers satisfaction. The purpose of this study was to analyze the level of performance, satisfaction, and the level of interest of farmer groups towards extension services in Purwosari Village, Mijen District, Semarang City. This research used 70 samples of farmer respondents that were selected using simple random sampling. Data were collected using interviews, observation, and documentation. Results of the Importance Performance Analysis (IPA) defines five attributes in quadrant I (Main Priority), three attributes in quadrant II (Maintain Achievement), two attributes in quadrant III (Low Priority), and four attributes in quadrant IV (Excessive). The result of the Customer Satisfaction Index (CSI) describes that the performance attributes of agricultural extension is 65.6%. This value (in the range of 33.4% - 66.5%) identifies that overall farmers in Purwosari Village were quite satisfied with the performance of agricultural extension workers.